Percutaneous Coronary Intervention in Older Patients with ST-Elevation Myocardial Infarction and Cardiogenic Shock - Damluji, Abdulla A. (J Am Coll Cardiol, 2019)
BACKGROUND: Older adults ≥75 years of age carry an increased risk of mortality after ST-elevation myocardial infarction (STEMI) complicated by cardiogenic shock. OBJECTIVES: To examine the use of percutaneous coronary intervention (PCI) in older adults with STEMI and shock and its influence on in-hospital mortality. METHODS: We used a large publicly available all-payer inpatient health care database sponsored by AHRQ between 1999 to 2013. The primary outcome was in-hospital mortality. The influence of PCI on in-hospital mortality was assessed by quintiles of propensity score (PS). RESULTS: Of the 317,728 encounters with STEMI and shock in the U.S., 111,901 (35%) were adults ≥75 years. Of these, 53% were females and 83% were Caucasians. The median [IQR] number of chronic conditions was 8 [6,10]. The diagnosis of STEMI and cardiogenic shock in older patients decreased significantly over time (proportion of older adults with STEMI and shock: 1999: 42% vs. 2013: 29%). Concomitantly, the rate of PCI utilization in older adults increased (1999: 27% vs 2013: 56%, p <0.001), with declining in-hospital mortality rates (1999: 64% vs. 2013: 46%, p <0.001). Utilizing PS matching methods, PCI was associated with lower risk of in-hospital mortality across quintiles of propensity score (Mantel-Haenszel OR: 0.48, 95% CI 0.45–0.51). This reduction in hospital mortality risk was seen across the 4 different United States census bureau regions (Adjusted OR: Northeast: 0.41, 95% CI 0.36–0.47; Midwest: 0.49, 95% CI 0.42–0.57; South: 0.51, 95% CI 0.46–0.56; West: 0.46, 95% CI 0.41–0.53). CONCLUSIONS: This large and contemporary analysis shows that utilization of PCI in older adults with STEMI and cardiogenic shock is increasing and paralleled by a substantial reduction in mortality. While clinical judgement is critical, older adults should not be excluded from early revascularization based on age in the absence of absolute contraindications.